2001
DOI: 10.1080/09581590010028246
|View full text |Cite
|
Sign up to set email alerts
|

Problems in doctor-patient communication: The case of younger women with breast cancer

Abstract: AB S T R A C T Communication between physicians and patients is considered to be a core component in the provision and receipt of appropriate medical care. However, previous research indicates that doctor-patient relationships can be problematic, with negative consequences for patients including higher levels of anxiety, distrust of medical providers, dissatisfaction with healthcare and lower quality of life. This research utilizes data collected from a series of focus groups involving 19 women with breast can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 52 publications
(75 reference statements)
0
15
0
2
Order By: Relevance
“…A 1994 study on the preferences of women undergoing mammography revealed that 90% of respondents agreed that the radiologist should give them the results directly on site [24]. This desire is confirmed by a public health journal with regard to young women affected by breast cancer and their desire to be informed of their fate [25]. In the same year, the concept was restated that information and a more direct involvement of the patient in decision making improved patient satisfaction as well as outcome, as it had a positive impact on functional recovery and quality of life and increased acceptance of oncological therapies [26].…”
Section: Why Communicate?mentioning
confidence: 98%
See 1 more Smart Citation
“…A 1994 study on the preferences of women undergoing mammography revealed that 90% of respondents agreed that the radiologist should give them the results directly on site [24]. This desire is confirmed by a public health journal with regard to young women affected by breast cancer and their desire to be informed of their fate [25]. In the same year, the concept was restated that information and a more direct involvement of the patient in decision making improved patient satisfaction as well as outcome, as it had a positive impact on functional recovery and quality of life and increased acceptance of oncological therapies [26].…”
Section: Why Communicate?mentioning
confidence: 98%
“…Un'inchiesta eseguita nel 1994 sui desideri di donne sottoposte a mammografia dimostrò che più del 90% delle intervistate era d'accordo sul fatto che il radiologo dovesse fornire la diagnosi direttamente alle interessate [24]. La stessa aspirazione viene sancita su di una rivista di sanità pubblica a proposito della volontà di conoscere il proprio destino da parte di giovani donne affette da carcinoma mammario [25]. Nello stesso anno viene ribadito il concetto che già l'esperienza di molti aveva suggerito, che una migliore informazione e un più diretto coinvolgimento della paziente nelle decisioni dimostrava avere un effetto positivo sia nella soddisfazione della donna, sia nel suo out-come, ovvero come ricaduta positiva nel recupero funzionale e sulla qualità di vita, anche per una migliore accettazione delle terapie oncologiche [26].…”
Section: Why Communicate?unclassified
“…[35][36][37][38][39] The results of a focus group study suggest that the physician-patient relationship can be problematic, however, for younger (defined as younger than 50 years) women with breast cancer. 11 Research on other patient populations shows that poor communication between physicians and patients is significantly associated with high levels of anxiety, distrust of health care providers, suspicion of therapy recommendations, and dissatisfaction with medical services [40][41][42][43][44] ; these factors may influence patients to try CT.…”
Section: Medical Decision Making and The Patient-physician Relationshipmentioning
confidence: 99%
“…On average, satisfaction with treatment decision making was high, with a mean score of 15.6 (SD = 3.4; range, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Most women reported that they were satisfied or very satisfied with the amount of time they had to make treatment decisions (92%) and with their degree of participation in the decision-making process (93%).…”
Section: Satisfaction and Ct Usementioning
confidence: 99%
See 1 more Smart Citation